Three-phase Hollow fiber Liquid-phase Micro Extraction for Determination and Analysis of Terazosin in Biological Fluids Via High Performance Liquid Chromatography at Trace Levels - Emadzadeh, Sahel; Qomi, Mahnaz; Saadat, Mohammadreza; Piroozi, Foroozan (Current Analytical Chemistry, 2016)
New hollow fiber based liquid phase microextraction (HF-LPME) technique followed by high performance liquid chromatography (HPLC) coupled with ultraviolet (UV) detector was introduced for detection and determination of terazosin in urine and plasma samples. The effect of different parameters which influence extraction efficiency such as organic membrane solvent, donor/acceptor phase composition, extraction time, stirring rate, salt concentration and extraction temperature were studied. Following optimization, extraction recoveries more than 86% were obtained in different biological matrices which resulted in preconcentration factors higher than 161 and an acceptable repeatability (1.25 < RSD% <2.30, n=3). The method presents good linearity with coefficiency higher than 0.9994. Finally, the proposed method was applied for detection and determination of terazosin in urine and plasma samples.
Keywords: hollow fiber liquid phase microextraction